One-pot synthesis for gradient copolymers via concurrent tandem living radical polymerization: mild and selective transesterification of methyl acrylate through Al(acac)3 with common alcohols. Issue 42 (28th July 2021) - Huynh, Tam Thi-Thanh; Kim, Si Eun; Kim, Soon Cheon; Kim, Jin Chul; Park, Young Il; Jeong, Ji-Eun; Yeo, Hyeonuk; Lee, Sang-Ho
Abstract : The acrylate based gradient copolymers were successfully synthesized by concurrent tandem living radical polymerization using Al(acac)3 as cocatalyst with common alcohols. Abstract : A series of gradient copolymers were synthesized by the ruthenium-catalyzed living radical polymerization (LRP) of methyl acrylate (MA) and aliphatic alcohols using aluminum acetylacetonate Al(acac)3 . In this polymerization system, Al(acac)3 was successfully used not only as an additive for the Ru-catalyzed LRP but also as a catalyst for the selective transesterification of an unsaturated ester monomer in mild conditions in a process known as concurrent tandem living radical polymerization. The resulting MA-based gradient copolymers showed well-controlled molecular weight and distribution in a one-pot reaction and exhibited a well-controlled gradient sequence in their polymer chain. Control of transesterification and the metal-catalyzed living radical polymerization (Mt-LRP) rate varied depending on the concentration of the Al(acac)3 and the structure of varying alcohols, which were confirmed by 1 H NMR, SEC, and DSC analysis. In particular, this research opens a new synthetic methodology for preparing acrylate-based gradient copolymers via concurrent tandem LRP not limited to the synthesis of methyl methacrylate types of gradient copolymers.